Effect of fish gelatine-sodium alginate interactions on foam formation and stability. (March 2019) - Phawaphuthanon, Natthiya; Yu, Daeung; Ngamnikom, Peerapong; Shin, Il-Shik; Chung, Donghwa
Abstract: The effect of fish gelatine (FG)−alginate (AL) interactions on the formation and stability of foams was investigated by examining relationships between surface, bulk, and foaming properties of aqueous mixtures of FG and AL at 25 °C under different values of pH and FG:AL ratio. Replacing a portion of FG with AL (FG:AL ratio = 80:20, 50:50, and 20:80) at pH 5.0 or 7.0 increased the air-liquid surface tension, negative electrophoretic mobility, bulk viscosity, and particle size of FG−AL mixtures. At pH 3.5 (below the isoelectric point of FG), the AL replacement increased the particle size more dramatically; however, it suppressed trends of increasing negative electrophoretic mobility and bulk viscosity, and even reduced the surface tension, due to stronger electrostatic attractions between oppositely charged FG and AL molecules and the resulting formation of more charge-neutralised FG−AL complexes. Foaming ability became stronger as the surface tension decreased, the negative electrophoretic mobility approached to zero (more charge-neutralised), and the bulk viscosity decreased; however, it was not closely correlated with particle size. FG−AL mixtures had a weaker foaming ability than solutions prepared only with FG or whey protein concentrate; however, these mixtures exhibited much higher foam stability during storage at 25 °C. FG−AL mixtures prepared at pH 3.5 and a FG:AL ratio of 80:20 showed the best foaming ability and foam stability. Graphical abstract: Image 1 Highlights: FG−AL interactions strongly influenced the foaming properties of FG−AL mixtures. Surface, bulk, and foaming properties of FG−AL mixtures were mutually related. FG−AL mixtures had a weaker foaming ability than FG or whey protein solutions. FG−AL mixtures showed greater foam stability than FG or whey protein solutions. FG−AL mixtures showed the best foaming properties at pH 3.5 and FG:AL = 80:20.